Sintesis Nanopartikel Minyak Atsiri Gardenia Menggunakan Lapisan Pelindung PolimerPeg-40 Hydrogenated Castor Oil Dan Karakterisasinya - Mario Epindonta; Horasdia Saragih (Journal of Pharmaceutical and Sciences, 2026)
This study focused on the preparation of Gardenia essential oil nanoemulsions using PEG-40 Hydrogenated Castor Oil (PEG-40 HCO) as a surfactant through an atomization method to evaluate the effect of oil concentration on the physical characteristics and electrokinetic properties of the resulting system. Four oil volumes, namely 4, 6, 8, and 10 mL in 80 mL of water, were used as precursors and subsequently analyzed to determine particle size, polydispersity index (PDI), electrophoretic mobility, and zeta potential. The results showed that increasing oil concentration tended to increase the average particle diameter. The obtained PDI values were relatively low; however, their interpretation was conducted cautiously because the system exhibited a bimodal particle size distribution. The zeta potential values ranged from −2.3 to −7.8 mV, while the electrophoretic mobility values ranged from −0.000017 to −0.000060 cm²/Vs. These results indicate changes in particle surface characteristics with increasing essential oil concentration. The characteristics of the resulting nanoemulsion suggest that PEG-40 HCO plays a role in the formation and dispersion of oil droplets in an aqueous medium. Overall, the findings indicate that PEG-40 HCO has potential for the preparation of Gardenia essential oil nanoemulsions with particle sizes in the nanometer range and relatively favorable size distribution characteristics, making them promising for further development in water-based perfume formulations and other cosmetic applications. However, the long-term stability of the system still requires further stability evaluation.